2019
DOI: 10.1002/term.2910
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the decellularization process of human maxillofacial muscles for facial reconstruction using a detergent‐only approach

Abstract: Trauma, congenital diseases, and cancer resection cause muscle deformities of the human facial muscle. Muscle defects are either treated with local or distal flaps if direct closure is not possible. However, such surgical interventions are limited by donor morbidity and limited tissue availability. Decellularized scaffolds provide alternative strategies for replacing and restoring missing facial muscle by creating scaffolds that mimic the native tissue. This study aimed to develop a protocol to decellularize h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Overall, the DOT protocol has been successful in decellularizing both human FDS and maxillofacial muscles to produce a tissue scaffold . This study highlights the broad application of DOT protocols for decellularization of skeletal muscle.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Overall, the DOT protocol has been successful in decellularizing both human FDS and maxillofacial muscles to produce a tissue scaffold . This study highlights the broad application of DOT protocols for decellularization of skeletal muscle.…”
Section: Discussionmentioning
confidence: 74%
“…All steps for decellularization of the muscle were carried out as per the previous article which included three protocols. The detergent only treatment (DOT) used 2% sodium dodecyl sulfate (SDS) for decellularization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that Collagens are responsible for for maintaining the ECM structure. [26] Although it is widely considered decellularization with SDS is related to ECM ultrastructure disruption [27,28] but our SEM results demonstrated that the 3D ECM structures were preserved thus indicating that 1% SDS was safe to DTG scaffolds. Besides, LN and FN are involved in cell adhesion.…”
Section: Discussionmentioning
confidence: 71%